FootNotes: Geo-referenced Audio Annotations for Nonvisual Exploration - Gleason, Cole; Fiannaca, Alex; Kneisel, Melanie; Cutrell, Ed; Morris, Meredith Ringel (Proceedings of the ACM on Interactive, Mobile, Wearable and Ubiquitous Technology (IMWUT 2018), 2018)
The majority of information in the physical environment is conveyed visually, meaning that people with vision impairments often lack access to the shared cultural, historical, and practical features that define a city. How can someone who is blind find out about the sleek skyscrapers that dot a modern city’s skyline, historic cannons that have been remade into traffic pillars, or ancient trees that uproot a neighborhood’s sidewalks? We present FootNotes, a system that embeds rich textual descriptions of objects and locations in OpenStreetMap, a popular geowiki. Both sighted and blind users can annotate the physical environment with functional, visual, historical, and social descriptions. We report on the experience of ten participants with vision impairments who used a spatialized audio application to interact with these annotations while exploring a city. By sharing rich annotations of physical objects and areas, FootNotes helps people thoroughly explore a new location or serendipitously discover previously unknown features of familiar environments.